AN EXPLORATION OF OUTDOOR EDUCATION AND THE SHAPING OF NATIONAL VALUES IN SINGAPORE - Zhu, Meilan; Abdul Razak, Ateerah; Jamalludin, Nur Hafifah (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Outdoor education plays a key role in cultivating national values. Singapore's outdoor education system is closely linked to the cultivation of national values and is of great significance. Starting from the educational objectives, this study explores how the national educational objectives at different stages of Singapore's post-independence period have affected the requirements for outdoor education and national values. The aim is to provide a reference for the study of education in China.